Acupuncture as an adjuvant treatment for diabetic neuropathy: a systematic literature review (Research, Society and Development, 2022)
Acupuncture is one of the therapies used as adjuncts for the treatment of diabetic neuropathies, which is a complication of diabetes mellitus, aiming to analyze whether acupuncture can be used as an adjuvant and non-pharmacological treatment for diabetic neuropathy. This study is a systematic literature review using the PRISMA method, in which searches were performed in the following databases: PubMed, Medline, ClinicalTrials Regarding the results, 145 articles were found, which considered the following selection criteria: approach of acupuncture in the adjuvant treatment of patients with diabetic neuropathy, texts in English, Spanish and Portuguese, with publications between the years 2017 to September 2022. Following the guidelines of the PRISMA method, the research was divided into four phases: identification, screening, eligibility and inclusion and 12 articles were used for the development of this work. Therefore, it is concluded that studies and clinical trials with animals and humans have demonstrated satisfactory improvements in symptoms, contributing to the reduction of risks in diabetic neuropathy.